Optimizing mycorrhizal fungi application for improved nutrient uptake, growth, and disease resistance in cardamom seedlings (Elettaria cardamomum (L.) Maton) - Sarathambal Chinnathambi; Mohammed Faisal Peeran; Veeraraghavan Srinivasan; Sivasankaran Mukesh Sankar; Priya George (Heliyon, 2024)
This study evaluated the impact of various doses (5, 10, 15 g) and application sequences (1, 2, or 3 times at monthly intervals) of arbuscular mycorrhizal (AM) fungal inoculum on cardamom seedlings over two years (2020–2021 and 2021–2022). The results indicated that the dosage of AM inoculum had a more substantial effect on the seedlings than the application sequence. A 10 g dose significantly increased shoot length and dry weight, while three applications of 5 g each improved the number of fibrous roots. Although potassium uptake was not affected, phosphorus and calcium uptake were highest with the 10 g dose. Arbuscular mycorrhizal inoculation also enhanced phosphatase activity in the rhizosphere, with 5 g improving acid phosphatase and 10 g improving alkaline phosphatase activity. Disease incidence, including seedling rot was lower with the 10 g dose, and additional sequential applications did not further reduce disease. Structural equation modeling (SEM) revealed that AM colonization positively influenced dry weight through the number of fibrous roots, showing a strong relationship between AM dose, colonization, spore count, and mycorrhizal dependency. This study indicates that applying a 10 g dose of AM fungal inoculum can be particularly beneficial in agroecosystems for improving cardamom seedling growth, nutrient uptake, and disease resistance.